Climacteric and menopause: epidemiology and pathophysiology - Salvador, Jorge (2015)
We present the results of an up-to-date review on climacteric, menopause, post menopause, epidemiology, pathophysiology and clinical presentation concepts. It is necessary to consider these aspects in order to adequately treat hypoestrogenism characterizing this group of patients.